2010
DOI: 10.1073/pnas.1006402107
|View full text |Cite
|
Sign up to set email alerts
|

Attractive noncovalent interactions in asymmetric catalysis: Links between enzymes and small molecule catalysts

Abstract: Catalysis by neutral, organic, small molecules capable of binding and activating substrates solely via noncovalent interactions-particularly H-bonding-has emerged as an important approach in organocatalysis. The mechanisms by which such small molecule catalysts induce high enantioselectivity may be quite different from those used by catalysts that rely on covalent interactions with substrates. Attractive noncovalent interactions are weaker, less distance dependent, less directional, and more affected by entrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
436
0
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 686 publications
(460 citation statements)
references
References 54 publications
5
436
0
17
Order By: Relevance
“…It has been known for decades that substrate organization is one of the major modes of assistance that enzymes provide in accelerating selective catalysis. More recently similar phenomena have been convincingly documented in reactions catalyzed by synthetic organic molecules (35). Herein we have shown that one of the at least five important roles of an even smaller molecule, water, is organization of a substrate much larger than itself.…”
Section: Discussionmentioning
confidence: 48%
“…It has been known for decades that substrate organization is one of the major modes of assistance that enzymes provide in accelerating selective catalysis. More recently similar phenomena have been convincingly documented in reactions catalyzed by synthetic organic molecules (35). Herein we have shown that one of the at least five important roles of an even smaller molecule, water, is organization of a substrate much larger than itself.…”
Section: Discussionmentioning
confidence: 48%
“…To be more precise, as recently elucidated by Jacobsen, many different interactions are often cooperating within the reaction mechanism in order to lead to high enantioselectivities [37]. The known non-covalent interactions scope includes charge-charge, charge-dipole, dipole-dipole, charge-induced dipole, dipoleinduced dipole forces, steric repulsion and H-bond ( Figure 9).…”
Section: Non-covalent Organocatalysismentioning
confidence: 99%
“…Hydrogen bonding interactions play a key role in noncovalent organocatalysis, [33][34][35] thus determination of pK a values facilitate the understanding of catalytic activity and catalyst design. However, the equilibrium values have their limitations for a kinetic property such as transition state stabilization.…”
Section: Pk a Measurementsmentioning
confidence: 99%